Gamification improves antidepressant effects of cognitive control training-A pilot trial - Simone Weller; Philipp A. Schroeder; Christian Plewnia (Frontiers Media S.A., 2022)
ObjectiveComputerised cognitive trainings have been put forward to improve control over negatively biased information processing and associated depressive symptomatology. Yet, disease-related impairments of motivation and endurance, as well as insufficient accessibility hinder use of this promising therapeutic opportunity. Here, we developed an app (de:)press©) that utilizes a cognitive control training (paced auditory serial addition task) enriched with gamification and information elements. We compared a six-week training with de:)press© to a non-gamified version (active control group).MethodsThirty-two depressed participants were included. Each received either de:)press© or the non-gamified version and was instructed to train three times per week for two weeks. Afterwards (four weeks) they were free to train at their own discretion. Depression severity was assessed during training and two follow-up sessions. Primary endpoint was defined as difference between groups [change of Montgomery-Åsberg Depression Rating Scale (MADRS)] four weeks after end of training.ResultsDepression severity decreased in both groups. At primary endpoint, MADRS scores were significantly lower in the de:)press©-group compared to the control group. No differences were observed at three months' follow-up. Intervention usability was consistently rated positively. Participants who had trained with de:)press© maintained the recommended training frequency without further prompting. Besides transient fatigue or frustration, no adverse effects were observed.ConclusionThis pilot demonstrates that gamification and information elements can substantially increase cognitive control training efficacy in alleviating depressive symptoms. Moreover, it provides first evidence for the feasibility and efficacy of de:)press© as an add-on intervention to treat depression.Clinical trial registrationThe study is registered under ClinicalTrials.gov, identifier: NCT04400162.